Distribution and biosynthesis of LH-RH and structurally related peptides - Dutlow, Clive M (Division of Chemical Pathology, 2018)
Biologically active peptides are a class of molecules which can, in general, be grouped into families of structurally related moieties which have a wide somatic distribution and which subserve multiple physiological roles. Thus, the releasing factors of the hypothalamus or their structural analogues may carry out multiple endocrine, paracrine, or neurotransmitter functions outside the hypothalamus. This thesis describes the distribution and biosynthesis of Luteinizing Hormone-Releasing Hormone (LH-RH) and structurally related peptides in mammalian tissues and tumours. Two strategies were employed in this investigation: (a) Immunological screening of tissues for suitable sources of LH-RH and the partial characterization of the LH-RH immunoreactive peptides of selected tissues; (b) Complementary oligonucleotide screening of mRNA from certain tissues, cDNA and genomic libraries as well as genomic DNA restriction endonuclease fragments to establish the nature of the LH-RH precursor and related molecules. Acetic acid extracts of nineteen rat tissues were assayed in serial dilution for LH-RH immunoreactivity (LH-RH-IR). An antibody directed to the middle of the LH-RH sequence was used in these screening radioimmunoassays. LH-RH-IR was found in extrahypothalamic brain areas, in gastroenteropancreatic tissues, in the retina, the submandibular gland, the thyroid and the testes. In view of a putative role of endogeonous LH-RH-like immunoreactive peptides in intra-testicular regulation, the molecular nature of the LH-RH-like material detected in rat testes was investigated. Acetic acid extracts of adult rat testes were partially purified by LH-RH-immunoaffinity chromatography. On Sephadex G-100 this material separated into four major peaks of >100K, ~32K, ~5K and <4K daltons. The <4K peak of LH-RH-IR eluted differently on Sephadex G-25 and analytical reverse phase HPLC than did synthetic hypothalamic LH-RH decapeptide. Antibodies directed at the C-terminus of LH-RH gave higher estimates of LH-RH-IR for all the chromatographically separated testicular polypeptides than did N-terminally and middle directed antisera. The small testicular LH-RH-like peptides displaced radiolabelled LH-RH agonist from rat pituitary membranes more effectively than did the larger immunoreactive molecules. Monkey, pig and dog testes as well as dog Sertoli cell tumours were extracted with acetic acid and shown to contain LH-RH immunoreactive material similar to that of the rat. Human seminal plasma was also investigated as a source of LH-RH-IR. When pooled seminal plasma from azoospermic males was fractionated by gel filtration some fractions had significant amounts of the rat testicular type of LH-RH.